2009
DOI: 10.1073/pnas.0902869106
|View full text |Cite
|
Sign up to set email alerts
|

CD39 deletion exacerbates experimental murine colitis and human polymorphisms increase susceptibility to inflammatory bowel disease

Abstract: CD39/ENTPD1 hydrolyzes proinflammatory nucleotides to generate adenosine. As purinergic mediators have been implicated in intestinal inflammation, we hypothesized that CD39 might protect against inflammatory bowel disease. We studied these possibilities in a mouse model of colitis using mice with global CD39 deletion. We then tested whether human genetic polymorphisms in the CD39 gene might influence susceptibility to Crohn's disease. We induced colitis in mice using Dextran Sodium Sulfate (DSS). Readouts incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
268
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 260 publications
(289 citation statements)
references
References 39 publications
19
268
0
2
Order By: Relevance
“…These findings are consistent with previous reports that ATP and adenosine exacerbates and protects against gut inflammation, respectively 37, 38, 39, 40. Mice deficient in NTPDases have more severe DSS‐induced colitis, and human ENTPD1 gene polymorphisms increased IBD susceptibility and also affected the homeostasis of the immune system 9, 36. Our results indicate that these protective roles of NTPDases are also likely to be mediated through modulating innate immune responses (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous reports that ATP and adenosine exacerbates and protects against gut inflammation, respectively 37, 38, 39, 40. Mice deficient in NTPDases have more severe DSS‐induced colitis, and human ENTPD1 gene polymorphisms increased IBD susceptibility and also affected the homeostasis of the immune system 9, 36. Our results indicate that these protective roles of NTPDases are also likely to be mediated through modulating innate immune responses (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…POM‐1 inhibits phosphohydrolysis of ATP by selectively targeting NTPDases, especially NTPDase1 and NTPDase3, both overexpressed in human inflamed intestinal mucosa (Figure 1b) 35. It has been reported that global deficiency of NTPDase1 or NTPDase3 resulted in exacerbation of DSS colitis 9, 36. DSS administration induced similar body weight loss in both control and POM‐1‐treated mice.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To date, eight E-NTPDases have been identified in humans, where four of them, NTPDases 1, 2, 3, and 8 are found to be expressed on the plasma membrane [9,10]. NTPDase 1/CD39, the prototype of this family, plays a key role in mediating inflammation in disease entities such as acute lung injury [11], inflammatory bowel disease [12,13], diabetic nephropathy [14], and ischemic reperfusion injury [15]. Originally described as a B lymphocyte activation marker, CD39 is also expressed on endothelial cells and recently identified on circulating microparticles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Estes marcadores estão funcionalmente ativos e possuem ação como indutores da adenosina pericelular (Deaglio et al, 2007). Assim, tendo em vista que um dos mecanismos de ação do MTX é manter os níveis de adenosina extracelular elevados e a importância da atividade das ectonucleotidases em gerar adenosina (Kobie et al, 2006;Friedman et al, 2009) -(direita) de indivíduos sadios (IS)( n = 5),pacientes R-MTX( n = 6) e UR-MTX( n = 6).Os gráficos representam a média ± SEM. *P < 0.05 comparado ao grupo IS.…”
Section: -Expressão De Cd39 E Cd73 Em Linfócitos Tcd4 + De Pacientesunclassified